PENGUATAN KAPASITAS GURU DAN SANTRI MELALUI IMPLEMENTASI SISTEM PENDIDIKAN DIGITAL DI PONDOK PESANTREN PPAI DARUN NAJAH 2 MALANG - Muhammad Muharrom Al Haromainy; Afina Lina Nurlaili; Ryan Purnomo; Theressa Marry Christianty; Luthfiyana Mahrurin Abadi (Universitas Mataram, 2026)
The development of digital technology has driven significant changes in modern education systems, including religious-based institutions such as Islamic boarding schools. As Islamic educational institutions, pesantren are required to adapt to digitalization to improve institutional management and learning processes effectively. This digital transformation involves not only the adoption of technology but also the enhancement of human resource capacity within the institution. Therefore, the readiness of teachers and students becomes a crucial factor to ensure that digital education can be implemented optimally. This program aims to strengthen the capacity of teachers and students through the implementation of a digital education system at the Islamic Boarding School PPAI Darun Najah 2 Malang. The strengthening effort includes improving teachers’ technical abilities in using digital administrative and learning systems, as well as expanding students’ digital literacy. A total of 20 teachers participated in this program, while the number of students involved in the mentoring process reached 250. All objectives are directed toward encouraging the pesantren to transform into an educational institution that is responsive to technological advancements. The community service activities were carried out through phases of needs analysis, system design, and implementation of digital features such as the new student registration system, inventory system, e-learning platform, and library website. This process was continued with socialization for teachers and training sessions on digital literacy and the introduction of artificial intelligence technology for students. The results of the program showed a significant increase in digital competence among teachers after completing the training activities. Their initial understanding, which averaged 72.67%, increased to 98% following the system implementation and mentoring sessions. Teachers were able to operate the registration, inventory, and e-learning systems with greater confidence and accuracy. Furthermore, students gained new insights into the basic concepts of AI and its relevance to education and everyday life. This increase in knowledge also fostered higher learning motivation and a growing interest in digital technology among the students. In conclusion, the implementation of the Digital Education System in the pesantren has proven effective in improving administrative management, expanding access to learning, and strengthening the digital literacy of both teachers and students.